Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Menggunakan Media Kartu dan Ular Tangga pada Hasil Belajar IPA Fisika Siswa - Roza, Media; Rahman, Roza (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2017)
The objective of this study is to determine students’ learning outcomes physic between Instruction Based Learning model using TGT type of media snake ladder compared to conventional learning in class VIII MTsN 1 Lubuk Basung. The hypothesis formulated in this research is "The application of cooperative learning model TGT with media cards and snakes and ladders results higher Physical Science learning with conventional learning in science teaching Physics.". The kind of this research is quasy experimental and the design of this study is a Randomized Control Only Design. The population of this study is all of students at class VII MTsN 1 Lubuk Basung academic year 2015/2016. The sample of this research take by used a random cluster sampling technique. The class VIII.5 obtained as an experimental class and control class as a class is VIII.4. This test is given at the end of the study sample class 25 objective questions. The technique used to test the hypothesis is to use an equation that estimated the average one-way through the t-test, for normally distributed data and data group has a homogeneous variance. The average score on the cognitive aspects of learning outcomes is an experimental class and control class 85.52, 73.17. Based on the analysis of data obtained, t = 4.25 and t table = 1.67. Because t obtained in the rejection of H0, ie 4.25> 1.67, the decision was rejected H0 and H1 accepted. This means that there is an increase in student learning outcomes by using model Problem Based Instruction with conventional learning in science teaching Physics class VIII MTsN 1Lubuk Basung